Peculiar structural features of the metacognitive subsystem of mental models of interactions of servicemen of the National Guard of the Russian Federation - Fedorishin, Michael Ivanovich; Perevozkina, Yulia M. (Известия Саратовского университета. Новая серия: Акмеология образования. Психология развития)
The relevance of the res earch is determined by a scientifi c terminological confusion regarding of the term “metacognitivism”, concerning the nature and interrelationships between various metacognitive parameters, which has become widespread in psychology. It also concerns professional experience of the National Guard of Russia servicemen, gained in the context of modern combat, and the infl uence of this experience on the structural organization of the metacognitive subsystem of mental models of military men. The research objective is to study the metasystem aspect of collective mental models of interaction of the servicemen of the Russian National Guard, including the analysis of the impact of combat experience on the structural organization of the metacognitive subsystem of mental models. The study hypothesizes that the structure of the metacognitive subsystem of the military men, who have combat experience in special military operation (SMO), will be more integrated compared to that of cadets. Participants: servicemen of the Russian National Guard, who participated in the special military operation (N = 161) aged from 21 to 43 (M = 33; SD = 1.57), third-year cadets (N = 340) aged from 20 to 24 (M = 22; SD =1.02) of Novosibirsk Military Institute of the National Guard Troops of the Russian Federation (Novosibirsk) (n =188), of Saint Petersburg Military Institute of the National Guard troops of the Russian Federation (St. Petersburg) (n = 152). Methods (tools): the Level of Refl exivity Questionnaire (A. V. Karpov, V. V. Ponomareva) was used to record the level of personal refl ection; the Metacognitive Awareness Inventory (G. Schraw, R. Dennison adapted by A. V. Karpov, I. M. Skityaeva) was used to study the control of self–knowledge – metacognitive involvement in activity; the Self-assessment of Metacognitive Knowledge and Metacognitive Activity Questionnaire (M. M. Kashapov, Yu. V. Skvortsova) was used to analyze an individual’s metacognitive knowledge and metacognitive activity. Results: the comparative analysis of intercorrelation matrices of metacognitive parameters in the samples of the servicemen with combat experience gained during SMO and of the cadets (servicemen without combat experience) indicates their heterogeneity (the express χ2-Karpov method). The main conclus ions: the organizational structure of the metacognitive subsystem of the cadets is less coherent than that of the SMO participants, which demonstrates qualitative diff erences in the intercorrelation matrices between the metacognitive parameters. This refl ects the assimilation of professional experience among servicemen as the formation of a semblance of a mental model of interaction while performing military tasks in the context of modern combating. Practical Significance: the results obtained reveal the necessity to include in the professional training of cadets the study of cases aimed at solving simulated military and combat situations in order to activate and enhance the integration of structural components of the metacognitive subsystem of mental models.